PENERAPAN DEEP LEARNING DALAM MENINGKATKAN EFEKTIVITAS PRAKTIK PENGALAMAN LAPANGAN (PPL) DI MA RIYADLUS SHOLIHIN BERBASIS PESANTREN - Wardhatus Sa`adah; Ika Widia Ningsih; Muhammad Ilham Mauludi; Irma Mila Karimah; Moch Husnan; Khoiriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the deep learning approach in enhancing the effectiveness of the Teaching Practice Program (PPL) at MA Riyadlus Sholihin, an Islamic boarding school–based institution characterized by strong religious values and traditional learning culture. Using a qualitative case study design, data were collected through observations, in-depth interviews, and documentation. The findings reveal that student teachers applied deep learning from the planning stage by designing instructional tools that emphasize conceptual understanding, higher-order thinking activities, and the integration of pesantren values. During the implementation stage, strategies such as small-group discussions, case analysis, and guided reflection significantly improved students’ motivation, participation, and deep comprehension of the learning materials. Moreover, the approach contributed to strengthening religious values and fostering moral awareness within the pesantren learning environment. Despite its effectiveness, the implementation of deep learning faced challenges, including hierarchical traditional learning culture, limited learning facilities, and varied levels of students’ academic readiness. Student teachers responded to these challenges through pedagogical adaptation, flexible methods, and differentiated instruction. Overall, the study concludes that integrating deep learning into PPL enhances pre-service teachers’ pedagogical competence, elevates the quality of instructional practices, and increases the relevance of teaching experiences within Islamic boarding school contexts.